Makna Rahasia Wahyu Pertama (Kajian Stilistika Al-Qur’an) - Muhammad Alghiffary (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2019)
In the midst of the repressive and compelling methods of Islamic da'wah, the first revelation was presented to remind the Prophet's da'wah method in the midst of the Quraysh community. The first revelation was made a material object, because it has a style of language associated with the method of propagation of the Prophet. In addition, the first revelation also opened the model of the Prophet's preaching. Stylistics as a formal object is able to parse language style to find a picture of the situation and context of the problem at that time. The domain of this article is morphological (al-mustawÄ al-awarfi). The morphological domain was chosen because it could represent the discussion of other domains. Through the descriptive method the research results are obtained that the Prophet's method of persuasion is obtained through the description of the disposal of objects in the word iqra 'as fi muta'addi. In this context the Messenger of Allah did not immediately order the Quraysh to read the scriptures they brought. The first revelation also provides conditions for preachers. One of the requirements needed by a preacher is the nature of the pious. This trait is obtained through a long effort and process. In addition, a preacher also must always repeat knowledge in order to gain firm conviction. In introducing God, Rasulullah used persuasive, latent, and careful methods. The word Rabbun is an antithesis of belief that is packaged in a singular form to awaken the Quraysh people about the nature of the One God.